Heterogeneity in effective VAT rates across native and migrant households in France, Germany and Spain - Michael Christl; Andrea Papini; Alberto Tumino (European Commission, Joint Research Centre (JRC), 2020)
This paper contributes to the literature on the distributional properties of VAT analysing who bears higher VAT payments between native and migrant household in France, Germany and Spain. The question is of interest both from a distributional and fiscal perspective, fitting the ongoing debate of the net fiscal impact of immigration. Using data from the 2010 EU HBS and a simple VAT calculator we show the existence of gaps in effective VAT rates between native and migrant households in France and in Spain, while no significant gap is observed in Germany. Our results also confirm the existing evidence on the regressivity of VAT with respect to income. These findings suggest that the fairness consequences of VAT reforms should be carefully assessed and advocate for the importance of considering indirect taxation when assessing the fiscal cost of migration.
Keywords: 330; VAT; redistribution; migration